Role of vitamin C in decrease the toxic in lead acetate and some physiological and Biochemical parameter in male rats - AL-Quraishi, Ibrahim O.S.; AL-Khalidi, Wisam A.W. (Al-Qadisiyah Journal of Pure Science, 2017)
The present study aimed to the role vitamin C in of reducing the toxic effects result from exposing to lead acetate. Male rat (Albino Rats) used the study, Injections interaperitoneal the lead acetate of concentration (4, 8, 12 mg/kg) for 4 weeks. Also administration vitamin C concentration (14 mg/kg) in the synchronically an non-synchronically manner of the exposure to lead acetate of concentration (4, 8, 12 mg/kg). The result studied according to the following: 1- Significant decrease (P<0.05) of RBC count, Hb concentration and PCV. especially in high concentrations of the experiment. 2- Significant increase (P<0.05) of total WBC count, Neutrophils and eosinophil count, especially in high concentration of the experiment. Beside significant decrease (P<0.05) of Lymphocytes count, but Monocytes increment the significant level (P>0.05) . 3- Significant decrease (P<0.05) of serum total protein, concentration which is increased by increase of concentration of exposure, significant increase (P<0.05) of cholesterol concentration, Triglyceride, and VLDL-C in serum of the high concentration of lead, while HDL-C its concentration significant increased (P<0.05) . The receiving vitamin C in a synchronically with ascending concentration lead acetate led to efficient improving in parameters including study in group (G3, G6, G9) the toxic effects of lead acetate and relieving is toxicological changes comparing with groups (G1, G4, G7)which were injected by lead only, or group administration vitamin C non synchronically (G2, G5, G8) the some the samples taken from the animals of the control group.The administration vitamin C in a non synchronically with lead acetate not led to any improving clearing in studying parameters especially in groups (G5, G7).Conclusions of study to of exposing to different concentration of lead acetate synchronically because effects negative in the physiological . improve this study administration vitamin C synchronically to role relation effect lead acetate .